Low Lattice Mismatch InSe–Se Vertical Van der Waals Heterostructure for High‐performance Transistors via Strong Fermi‐Level Depinning (Small Methods 8/2020). Issue 8 (13th August 2020) - Jiang, Jianfeng; Meng, Fanqi; Cheng, Qilin; Wang, Aizhu; Chen, Yuke; Qiao, Jie; Pang, Jinbo; Xu, Weidong; Ji, Hao; Zhang, Yu; Zhang, Qinghua; Wang, Shanpeng; et al.
Abstract : In article number 2000238, Hong Liu, Lin Han, and co‐workers present InSe‐Se vertical van der Waals (vdW) heterostructures to address a formidable contact engineering challenge, which have a low lattice mismatch of 1.1% and form 2D/2D low‐resistance vdW contacts, creating an InSe contact interface that substantially limits chemical disorder and Fermi‐level pinning.